1975
DOI: 10.1172/jci107960
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an H2-receptor antagonist on food-stimjlated acid secretion, serum gastrin, and gastric emptying in patients with duodenal ulcers. Comparison with an anticholinergic drug.

Abstract: A B S T R A C T The purpose of the present series of experiments was to measure and compare the effects of an anticholinergic drug (isopropamide) and an antagonist of the histamine H2 receptor (metiamide) on foodstimulated acid secretion. Patients with duodenal ulcers were stimulated by a steak meal, and acid secretion was measured by in vivo intragastric titration. The largest dose of isopropamide that can be taken clinically without producing intolerable side effects (maximum tolerated dose) suppressed food-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The effectiveness of vagotomy and of antrectomy in duiodenal ulcer disease results not only from the decrease in the direct stimulation of acid by vagal pathways and by gastrin, respectively, but also probably results from the respective removal of the cholinergic and gastrin components from the interactions that occur between secretagogues. H2-receptor antagonists have been remarkably effective agents in decreasing acid secretion in duodenal ulcer patients (36,37) and in patients with the Zollinger-Ellison syndrome (38). This effectiveness of H2-blockers has been taken as evidence that other secretagogues may act by, releasing histamine; the present data are not compatible with such a model as the only mechanism for secretagogue interaction.…”
Section: Discussionmentioning
confidence: 54%
“…The effectiveness of vagotomy and of antrectomy in duiodenal ulcer disease results not only from the decrease in the direct stimulation of acid by vagal pathways and by gastrin, respectively, but also probably results from the respective removal of the cholinergic and gastrin components from the interactions that occur between secretagogues. H2-receptor antagonists have been remarkably effective agents in decreasing acid secretion in duodenal ulcer patients (36,37) and in patients with the Zollinger-Ellison syndrome (38). This effectiveness of H2-blockers has been taken as evidence that other secretagogues may act by, releasing histamine; the present data are not compatible with such a model as the only mechanism for secretagogue interaction.…”
Section: Discussionmentioning
confidence: 54%
“…The same workers did however show a significantly greater gastrin response 150 min after an oxo meal in metiamide-treated subjects when compared to controls (4). On the other hand, Konturek et al (6) and Richardson et al (9) could not show any differences in gastrin levels between metiamide and controls after feeding when the gastric contents were kept at a constant pH. A recent longer term study in the rat showed a significant rise in gastrins and parietal cell hyperplasia after 18 days of feeding without controlling the gastric pH.…”
Section: Discussionmentioning
confidence: 88%
“…The effect of burimamide and metiamide on serum gastrin levels have been investigated in acute experiments or after short-term oral administration in a few studies (2,4,6,(8)(9)(10). In the main these studies have not shown any significant effect of these drugs on fasting stimulated serum gastrin levels although Barbezat et al (4) did find a statistically significant rise 150 min after an oxo meal in man, and Thomp son et al (10) showed that most patients had a rise in gastrin levels 1 week after metiamide therapy in duodenal ulcer patients.…”
mentioning
confidence: 99%
“…Acid secretion was measured for 2+ h by in vivo intragastric titration to pH 5.5, as described previously ( 18). The test meal consisted of 500 ml of a 5% aqueous solution of liver concentrate powder (Reheis Chemical Co., Chicago, 111.)…”
Section: Subjectsmentioning
confidence: 99%